Three cases of human Sarcocystis infection with a review of human muscular sarcocystosis in Malaysia - Pathmanathan, R.; Kan, S.P. (Royal Tropical Institute, 1992)
Three cases of muscular sarcocystosis from West Malaysia are reported. The morphological features of the parasites from these three cases are similar to the eight cases previously reported from this country. A review of this total of eleven cases of muscular sarcocystosis showed that they were all incidental findings, where man acted as intermediate hosts of as yet unknown Sarcocystis spp. These cases of muscular sarcocystosis were probably zoonotic in origin and associated with close contact with definitive hosts (both domestic and wild animals) thus permitting the contamination of food and drink with sporocysts shed by these definitive hosts. These infections were probably acquired locally as most of the subjects were born in Malaysia and none had ever left the country to stay elsewhere. Eight of the eleven cases reported were associated with malignancies, especially of the tongue and nasopharynx.